Immunopathological changes in case of the diabetes of the first type. The impact of the mother’s diabetes of the first type on the emryogenesis and fetogenesis of the fetus (Literature review, part II) - Kupriianova, L.; Ivanchenko, S. (Journal of Education, Health and Sport, 2022)
In the following article we have presented main risk factors of the development of the Diabetes Mellitus of the I type, as well as modern statistical data towards its correlation in a structure of the disease. We have revealed main markers of the disease, connected with the HLA system. We have also considered leading links in the pathogenesis of immunodeficiency development in case of patients with the Diabetes Mellitus of the I type relatively to the duration of the disease, presence of vascular complications as well as number of insulin units per day. We have provided clear criteria towards changes in the T-lymphocytes populations, what is prescribing changes in the helper-suppressor ratio. In addition, we have postulated that the autoimmune disorders, which are typical for the Diabetes Mellitus of the I type (DM of the I type) are leading to the increase in a number of apoptotically alteredd forms of T-lymphocytes, what is contributing to the deeping of changes in the immune system. Authors have studied main features of the interleukin-producing activity in case of patients with the DM of the I type. Namely: increased number of pro-inflammatory interleukins on the background of decrease of anti-inflammatory ones. The precise analysis has revealed, that there are circulating immune complexes in the blood of patients with DM of the I type, which are leading microcirculation’ disorders. The alterations, that were postulated and described relatively to the organism of patients with DM of the I type, are indicating deep disorders in the immune system and the morphological features of the thymus has to be studied, as far as the thymus as a central organ of the immunogenesis in case of fetuses from mothers, who are suffering from the DM of thr I type, in the aim of development of immunodeficiency in patients. Alongside with the description of changes in the immune system in case of patients with the DM of the I type, in the following article we have provided a scientific views on changes in the embrion- and fetogenesis of the fetus under the influence of mother’s DM of the I type. In addition, we have described morphological features of the placenta structure in case of this pathology, as well as pathomorphological changes in the strucutre of internal organs of fetus under the influence of this pathology in the mother’s organism. It was postulated, that in case of children, who were born from mothers, who are suffering from the DM of the I type, there is a syndrome of diabetic feto- and embryopathy, which is developing and leading to the poliorganic failure in the subsequent ontogenesis.